Synthesis of Chitosan Microparticles Encapsulating Bacterial Cell-Free Supernatants and Indole Acetic Acid, and Their Effects on Germination and Seedling Growth in Tomato (Solanum lycopersicum). (14th November 2022) - Gonzalez-Montfort, Thania Soledad; Almaraz-Abarca, Norma; Pérez-y-Terrón, Rocío; Ocaranza-Sánchez, Erik; Rojas-López, Marlon
Abstract : Encapsulation of biostimulant metabolites has gained popularity as it increases their shelf life and improves their absorption, being considered a good alternative for the manufacture of products that stimulate plant growth and fruit production. Cell-free supernatants (CFS) were obtained from nine indole-3-acetic acid (IAA) producing bacterial strains. Stenotrophomonas maltophilia (PT53T) produced the highest concentration of IAA (15.88 μ g/mL) after 48 h of incubation. CFS from this strain, as well as an IAA standard were separately encapsulated in chitosan microparticles (CS-MP) using the ionic gelation method. The CS-MP were analyzed by Fourier transform infrared spectroscopy (FTIR), showing absorption bands at 1641, 1547, and 1218 cm −1, associated with the vibrations of the carbonyl C=O, the N-H amine, and the bond between chitosan (CHI) and sodium tripolyphosphate (TPP). The effects of unencapsulated CFS, encapsulated CFS (EN-CFS), and encapsulated IAA standard (EN-IAA) on germination and growth of seven-day-old tomato ( Solanum lycopersicum ) seedlings were studied. Results showed that both EN-CFS and EN-IAA significantly (p < 0.05 ) increased seed germination rates by 77.5 and 80.8%, respectively. Both CFS and EN-IAA produced the greatest increase in aerial part length and fresh weight with respect to the treatment-free test. Therefore, it was concluded that the application of EN-CFS or EN-IAA could be a good option to improve the germination and growth of tomato seedlings.